Single-stage flow diversion with adjunctive coiling for cerebral aneurysm: outcomes and technical considerations in 72 cases. (25th May 2018) - Bender, Matthew T; Jiang, Bowen; Campos, Jessica K; Lin, Li-Mei; Beaty, Narlin; Vo, Chau D; Zarrin, David A; Caplan, Justin M; Huang, Judy; Tamargo, Rafael J; Colby, Geoffrey P; Coon, Alexander L
Abstract : Background: Adjunctive coiling may improve occlusion outcomes when combined in a single stage with cerebral aneurysm flow diversion. This technique has not been well described. Objective: To present a series of aneurysm patients treated by single-stage flow diversion with adjunctive coiling, describing technical considerations and outcomes. Methods: This was a retrospective cohort study using an IRB-approved database of procedures performed at a single institution. Treatment selection was based on large aneurysm size, morphological irregularity, branch vessel location, and wide neck. Results: A total of 72 Pipeline with adjunctive coiling (PAC) procedures were performed on 69 patients. Average aneurysm size was 11.0 mm and 86% were wide-necked. Three progressively complex techniques were performed approximately equally: 27 sequential (38%), 23 jailed single-intermediate (32%), and 22 bifemoral jailed microcatheter (31%) cases. Aneurysm dome (P=0.0223) and neck size (P=0.001) increased with procedural complexity and there was a trend toward increased procedure length, radiation exposure, and stent thrombosis. A 'light' coil pack was used with an average packing density of 14% that did not vary by technique. Of the three major complications (4.2%), none were observed with the sequential approach (0%), one with the jailed single-intermediate (4.3%), and two with bifemoral cases (9.1%) (P=0.116). Complete occlusion was achieved in 85% of PAC cases at 6 months and 96% at 12-month follow-up angiography. Conclusions: There are multiple approaches to flow diversion with adjunctive coiling, each with technical challenges, suitable to different types of aneurysms. Flow diversion with coiling can expedite and improve occlusion outcomes without a significant increase in morbidity.